Motorcycle rust-proof lubricating chain wax and preparation method thereof

By using a special rust -proof lubricating chain wax on the motorcycle chain, the dry friction and rust problems caused by poor grease adhesion have been solved, and the good lubrication and rust prevention effects of the chain are achieved, and the service life of the chain is extended.

CN119331675AActive Publication Date: 2025-01-21GUANGZHOU YOUBEI MATERIAL TECH CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411457848.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-01-21
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The existing grease has poor adhesion on motorcycle chains, which often lacks oil during operation and causes dry friction, which leads to severe wear and rust of the chain.

Method used

A motorcycle anti-rust lubricating chain wax, its formula includes 67-93.5%basic oil, 5.1-25.6%composite lithium soap thick chemical, 2.4-10.5%adhesive, 0.1-2%antioxidant Agent, 0.5-5%polar pressure antie wear agent, 0.5-5%functional additives and 0.05-1%metal passivation agents. The wax forms a coating with good lubrication, rust and abrasion performance by specific formulas and preparation methods.

Benefits of technology

The wax can effectively improve the lubrication performance of the chain, prevent rust, extend the service life of the chain, and maintain a good lubrication effect under high temperature and high load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005090986550000101
    Figure BDA0005090986550000101
  • Figure BDA0005090986550000111
    Figure BDA0005090986550000111
Patent Text Reader

Abstract

The invention discloses motorcycle antirust lubricating chain wax and a preparation method thereof, and relates to the technical field of lubricating materials. The antirust lubricating chain wax comprises the following raw materials in percentage by weight: 67%-93.5% of base oil, 5.1%-25.6% of a composite lithium soap thickening agent, 2.4%-10.5% of a tackifier, 0.1%-2% of an antioxidant, 0.5%-5% of an anti-wear reagent at extreme pressure, 0.5%-5% of a functional aid and 0.05%-1% of a metal deactivator, wherein the sum of the weight percentages of the raw materials is 100%. The anti-rust lubricating chain wax prepared by the invention is applied to extreme pressure motorcycle chain lubrication, has good extreme pressure antiwear property, anti-rust property and melt stability, and can meet the performance requirements of motorcycle chain wax.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lubricating materials, and in particular to a motorcycle rust-proof lubricating chain wax and a preparation method thereof. Background Art

[0002] Chain type is a mechanical transmission element composed of chain links that can transmit each other. It can accurately transmit power and has many excellent characteristics such as stable transmission, constant speed ratio, strong adaptability and convenient maintenance. It is widely used in various mechanical transmission structures. Chain transmission is not only suitable for use under high torque and low speed, but also shows superiority in corrosive, humid environment and high-speed rotation. In addition to the engine driving the rear wheel through chain transmission, there is also a timing chain used inside the engine. Chains and sprockets are the main power transmission components of motorcycles. Due to the characteristics of the chain structure (chain links are connected by hinges) and the load during work (tight side and loose side), the normal failure form of the transmission chain is fatigue damage of chain parts and wear and elongation of the chain. Reducing friction is the main measure to increase the life of the chain and sprocket. Apply chain wax on the chain to lubricate the chain reasonably. Good lubrication can not only extend the service life, reduce noise, reduce wear on the sprocket, but also improve the power utilization of the engine.

[0003] Grease has poor adhesion and lubrication properties on motorcycle chains, which results in the grease on the chain being quickly thrown out by high-speed centrifugal force during the operation of the motorcycle, causing the motorcycle chain to often lack oil during actual use, and be in a dry friction state, resulting in serious chain wear, which can easily cause the chain to stretch, make abnormal noises, and even fail. With the loss of grease, the metal material of the chain reacts chemically and electrochemically with the environment to generate rust, causing the chain to rust. Summary of the invention

[0004] The object of the present invention is to provide a motorcycle anti-rust lubricating chain wax and a preparation method thereof, so as to solve the following technical problems:

[0005] The existing grease has poor adhesion on the motorcycle chain, causing the grease on the surface of the motorcycle chain to be thrown out under the action of centrifugal force. In actual use, there is often a lack of oil, resulting in dry friction of the chain. Not only is it easy to cause dry friction of the chain, but as the friction continues, the surface of the chain is eroded by moisture and corrosive media in the atmosphere, causing the chain to rust, further accelerating the damage of the chain.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A motorcycle anti-rust lubricating chain wax, comprising the following raw materials in percentage by weight: 67-93.5% base oil, 5.1-25.6% composite lithium soap thickener, 2.4-10.5% tackifier, 0.1-2% antioxidant, 0.5-5% extreme pressure anti-wear agent, 0.5-5% functional additive, 0.05-1% metal passivator, the sum of the percentages by weight of the raw materials being 100%;

[0008] The preparation method of the functional additive comprises the following steps:

[0009] S1: Add nano-silicon dioxide, aniline and hydrochloric acid solution into a reaction kettle, mix ammonium persulfate and distilled water evenly and add them into the reaction kettle, react at room temperature for 18-24 hours, filter, wash with acetone, and dry to obtain component 1;

[0010] S2: Add component 1, thioglycolic acid and anhydrous ethanol into a reaction kettle, control the temperature to 50-60°C, keep warm for 1-3 hours under stirring conditions, filter, wash and dry to obtain a functional additive.

[0011] Preferably, the hydrochloric acid solution in S1 is a 0.5-1 mol / L hydrochloric acid aqueous solution; the addition ratio of nano-silicon dioxide, aniline, hydrochloric acid solution, ammonium persulfate, and distilled water is 10g: 1-2g: 500-1000mL: 3-6g: 100-200mL.

[0012] Preferably, the addition ratio of component 1, thioglycolic acid and anhydrous ethanol in S2 is 10 g: 0.5-1 g: 100-200 mL.

[0013] Preferably, the base oil is any one of a polyether base oil and a paraffin base oil.

[0014] Preferably, the paraffinic base oil is any one of 75SN, 150SN, 400SN and 150BS.

[0015] Preferably, the polyether base oil is polyether base oil SDT-055a.

[0016] Preferably, the preparation method of the complex lithium soap thickener comprises the following steps:

[0017] C1: Add lithium hydroxide powder and deionized water into a reaction kettle, control the temperature at 70-80°C, and stir until the lithium hydroxide powder is completely dissolved to obtain a lithium hydroxide solution;

[0018] C2: Add 12-hydroxystearic acid and sebacic acid into the reaction kettle and disperse them evenly. Control the temperature at 95-105°C, add lithium hydroxide solution, and saponify for 1-3 hours under heat preservation conditions to obtain a composite lithium soap thickener.

[0019] Preferably, the addition ratio of lithium hydroxide powder and deionized water in C1 is 1 g: 5-10 mL.

[0020] Preferably, the addition ratio of 12-hydroxystearic acid, sebacic acid and lithium hydroxide solution in C2 is 8-20g: 2-10g: 24-64g.

[0021] Preferably, the tackifier is one of ethylene-propylene copolymer and polyisobutylene, or a mixture of the two.

[0022] Preferably, the ethylene-propylene copolymer is T614.

[0023] Preferably, the polyisobutylene is PB2400.

[0024] Preferably, the antioxidant is any one of an organic amine antioxidant or a phenolic antioxidant.

[0025] Preferably, the phenolic antioxidant is 2,6-di-tert-butyl-p-cresol or 2,6-di-tert-butyl-α-dimethylamino-p-cresol.

[0026] Preferably, the organic amine antioxidant is N-phenyl-α-naphthylamine or N-phenyl-N′-cyclohexyl-p-phenylenediamine.

[0027] Preferably, the extreme pressure anti-wear agent is one or a mixture of two or more of phosphorus-containing compounds, sulfur-phosphorus compounds, and sulfur-phosphorus-nitrogen compounds.

[0028] Preferably, the phosphorus-containing compound is a phosphate or a phosphite; the sulfur-phosphorus compound is a thiophosphate or triphenylthiophosphate; and the sulfur-phosphorus-nitrogen compound is an amine salt of a thiophosphate or a nitrogen-containing derivative of sulfur-phosphoric acid.

[0029] Preferably, the metal passivator is one or a combination of two or more of benzotriazole, benzotriazole derivatives, thiadiazole derivatives, and benzyl nickel phosphate.

[0030] A preparation method of motorcycle anti-rust lubricating chain wax comprises the following steps: according to the raw material ratio, adding base oil, composite lithium soap thickener and tackifier into a reaction kettle, controlling the temperature at 95-105°C, keeping the temperature under stirring for 0.5-1h, controlling the temperature at 115-125°C, and vacuuming and dehydrating; then adding antioxidant, extreme pressure anti-wear agent, functional additive and metal passivator in sequence, stirring and mixing for 0.5-1.5h, naturally cooling, grinding and dispersing, and obtaining anti-rust lubricating chain wax.

[0031] Preferably, the specific steps of vacuum dehydration are: controlling the temperature at 115-125° C., vacuuming to -0.08 MPa, and maintaining constant vacuum dehydration for 1.5-3 hours.

[0032] Beneficial effects of the present invention:

[0033] (1) The present application uses 12-hydroxystearic acid, sebacic acid and lithium hydroxide to react to prepare a composite lithium soap, and uses the composite lithium soap as a thickener to thicken the base oil to prepare a lithium-based grease. The colloidal structure of the lithium-based grease is a typical two-phase dispersion structure, which has special rheological properties. It maintains a certain shape without flowing at room temperature and low load with micro-changes, adheres to the contact surface without slipping, and when the temperature rises or reaches its yield stress, the lithium-based grease undergoes a viscosity change and begins to flow, so it has good lubrication, protection and sealing effects. The present application adds a thickener, an antioxidant, an extreme pressure anti-wear agent, a metal passivator and a functional additive to the lithium-based grease to prepare an extreme motorcycle anti-rust lubricating chain wax, which has good extreme pressure anti-wear, rust resistance and melt stability, and can meet the performance requirements of motorcycle chain wax. The grease prepared in the present application has excellent high and low temperature performance and a wide range of operating temperatures, less carbon deposition and coking, and the coke formed can be dissolved in new oil, which is conducive to extending the decoking cycle and ensuring long-term operation of the chain.

[0034] (2) The present application disperses nano-silica in a reaction medium of chemical oxidation polymerization, uses ammonium persulfate as a polymerization initiator, and dissolves aniline monomers in a hydrochloric acid solution to generate aniline cation radicals that are adsorbed on the surface of silica particles and polymerize in situ on the silica surface to form polyaniline-coated spherical core-shell silica composite particles, i.e., component one; the present application then utilizes the amino groups on the polyaniline molecular chain to react with thioglycolic acid to graft thiol groups on the silica surface to obtain a functional additive. The present application utilizes aniline to polymerize on the surface of nano-silica, so that the silica becomes a functional particle with passivation performance. The functional additive prepared in the present application is added to the chain wax. The organic modification of the silica surface not only makes the silica uniformly dispersed in the chain wax, but also the organic molecular chains on its surface assist the chain wax to form an excellent lubricating protective film on the friction surface during the friction process. During the operation of the chain, the thiol groups grafted on the silica surface and the aniline polymer effectively repair the wear marks caused by friction on the working interface, wherein the thiol molecular chains will dissociate and adsorb on the metal surface and produce metallized sulfur materials, and the aniline polymer will dissociate during the friction process to repair the wear marks. The functional additive utilizes the spherical core-shell structure of the organic molecular chains coated on the silica surface, and the synergistic effect plays an anti-wear and friction-reducing role in the chain wax, giving the chain wax excellent corrosion resistance and anti-wear and friction-reducing properties.

[0035] (3) The functional additive prepared in the present application is added to the chain wax. With the addition of the functional additive, the free base oil in the chain wax can be adsorbed, the consistency of the base oil can be increased, and the adhesion performance and good metal wetting performance of the chain wax can be improved. The present application adds functional additives to the chain wax to effectively adjust the chain wax. Since the chain wax uses a complex lithium soap as a thickener, and the metal ions in the thickener molecules have a catalytic oxidation effect on the chain wax base oil, the addition of functional additives effectively reduces the adverse effects of the complex lithium soap on the chain wax. The chain wax added with the functional additive prepared in the present application is easy to form an oil film at the working interface, and can still maintain good lubrication performance under long-term operation at high temperature, which can ensure that the chain is not easy to form oil droplets and splash when running at high speed. The grease prepared in the present application can meet the requirements of motorcycle chain sealing and rust prevention and lubrication during operation. DETAILED DESCRIPTION

[0036] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] Embodiment 1 The preparation method of the composite lithium soap thickener comprises the following steps:

[0038] C1: 1 g lithium hydroxide powder and 7 mL deionized water were added to a reactor, the temperature was controlled at 80°C, and the mixture was stirred until the lithium hydroxide powder was completely dissolved to obtain a lithium hydroxide solution;

[0039] C2: Add 20g 12-hydroxystearic acid and 5g sebacic acid into a reactor and disperse them evenly. Control the temperature at 100°C, add 64g lithium hydroxide solution, and saponify for 2h under heat preservation conditions to obtain a composite lithium soap thickener.

[0040] The preparation method of the functional additive of embodiment 2 comprises the following steps:

[0041] S1: 10 g of nano-silicon dioxide, 1 g of aniline, and 500 mL of 1 mol / L hydrochloric acid aqueous solution were added to a reactor, 3 g of ammonium persulfate and 100 mL of distilled water were mixed evenly, and then added to the reactor. The mixture was reacted at room temperature for 18 h, filtered, washed with acetone, and dried to obtain component 1;

[0042] S2: Add 10 g of component 1, 0.5 g of thioglycolic acid and 100 mL of anhydrous ethanol into a reaction kettle, control the temperature to 50°C, keep warm for 1 hour under stirring, filter, wash and dry to obtain a functional additive.

[0043] The preparation method of the functional additive of Example 3 comprises the following steps:

[0044] S1: 10 g of nano-silicon dioxide, 1.5 g of aniline, and 700 mL of 1 mol / L hydrochloric acid aqueous solution were added to a reactor, 4.5 g of ammonium persulfate and 150 mL of distilled water were mixed evenly and added to the reactor, reacted at room temperature for 21 h, filtered, washed with acetone, and dried to obtain component 1;

[0045] S2: Add 10 g of component 1, 0.7 g of thioglycolic acid and 150 mL of anhydrous ethanol into a reaction kettle, control the temperature to 55°C, keep warm for 2 h under stirring, filter, wash and dry to obtain a functional additive.

[0046] The preparation method of the functional additive of embodiment 4 comprises the following steps:

[0047] S1: 10 g of nano-silicon dioxide, 2 g of aniline, and 1000 mL of 1 mol / L hydrochloric acid aqueous solution were added to a reactor, 6 g of ammonium persulfate and 200 mL of distilled water were mixed evenly, and then added to the reactor. The mixture was reacted at room temperature for 24 h, filtered, washed with acetone, and dried to obtain component 1;

[0048] S2: Add 10 g of component 1, 1 g of thioglycolic acid and 200 mL of anhydrous ethanol into a reaction kettle, control the temperature to 60°C, keep warm for 3 h under stirring, filter, wash and dry to obtain a functional additive.

[0049] Embodiment 5 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0050] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Example 2, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0051] Embodiment 6 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0052] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Example 3, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0053] Embodiment 7 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0054] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Example 4, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0055] The preparation method of the functional additive of Comparative Example 1 comprises the following steps:

[0056] 10 g of nano-silicon dioxide, 1.5 g of aniline, and 700 mL of 1 mol / L hydrochloric acid aqueous solution were added to a reactor, and 4.5 g of ammonium persulfate and 150 mL of distilled water were mixed evenly and added to the reactor. The mixture was reacted at room temperature for 21 h, filtered, washed with acetone, and dried to obtain a functional additive.

[0057] The preparation method of the functional additive of Comparative Example 2 comprises the following steps:

[0058] 10 g of nano-silicon dioxide, 0.7 g of thioglycolic acid and 150 mL of anhydrous ethanol were added into a reaction kettle, the temperature was controlled at 55° C., the mixture was kept warm for 2 h under stirring, and then filtered, washed and dried to obtain a functional additive.

[0059] The preparation method of the functional additive of Comparative Example 3 comprises the following steps:

[0060] S1: 1.5 g aniline and 700 mL 1 mol / L hydrochloric acid aqueous solution were added to a reactor, 4.5 g ammonium persulfate and 150 mL distilled water were mixed evenly and added to the reactor, reacted at room temperature for 21 h, filtered, washed with acetone, and dried to obtain component 1;

[0061] S2: Add 10 g of nano-silicon dioxide, 0.7 g of thioglycolic acid, and 150 mL of anhydrous ethanol into a reaction kettle, control the temperature to 55°C, keep the temperature for 2 h under stirring, filter, wash, and dry to obtain component 2;

[0062] S3: Blending component one prepared in S1 with component two prepared in S2 to obtain a functional additive.

[0063] Comparative Example 4 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0064] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated under constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of nano-silica, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, the mixture was naturally cooled, and the mixture was ground and dispersed to obtain an anti-rust lubricating chain wax.

[0065] Comparative Example 5 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0066] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Comparative Example 1, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0067] Comparative Example 6 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0068] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Comparative Example 2, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0069] Comparative Example 7 A method for preparing a motorcycle anti-rust lubricating chain wax comprises the following steps:

[0070] 79.6 g of paraffin base oil 150SN, 10.3 g of the composite lithium soap thickener prepared in Example 1, and 3.4 g of ethylene-propylene copolymer T614 were added to a reactor, the temperature was controlled at 100° C., and the mixture was kept warm for 1 h under stirring. The temperature was controlled at 120° C., the mixture was evacuated to -0.08 MPa, and the mixture was kept warm and dehydrated in a constant vacuum for 3 h. Then, 0.6 g of 2,6-di-tert-butyl-α-dimethylamino-p-cresol, 1 g of thiophosphate, 5 g of the functional additive prepared in Comparative Example 3, and 0.1 g of benzotriazole were added in sequence, the mixture was stirred and mixed for 1 h, naturally cooled, ground and dispersed, and an anti-rust lubricating chain wax was obtained.

[0071] Performance Testing

[0072] (1) Non-working cone penetration: Tested according to GB / T 269-2023 "Determination of cone penetration of greases and petroleum greases". The test results are shown in Table 1-2;

[0073] (2) Dropping point: Tested in accordance with GB / T 3498-2008 “Determination of dropping point of lubricating grease over a wide temperature range”. The test results are shown in Table 1-2.

[0074] (3)45 # Steel corrosion: Tested according to SH / T 0331-1992 "Grease Corrosion Test Method", test results are shown in Table 1-2;

[0075] (4) Adhesion (normal temperature): tested according to Appendix A of SH / T 0496. The test results are shown in Table 1-2.

[0076] (5) Water resistance (normal temperature): tested according to SH / T 0109-1992 "Determination of water resistance of lubricating greases". The test results are shown in Table 1-2.

[0077] (6) Oxidation induction period: Tested according to SH / T 0193 “Determination of oxidation stability of lubricating oil (rotating oxygen bomb method)”. The test results are shown in Table 1-2.

[0078] (7) Anti-rust performance

[0079] a. Wet heat test: According to GB / T 2361-1992 "Wet heat test method for rust-proof grease", 45# steel is coated with rust-lubricating chain wax and the test is conducted for 30 days. The test results are shown in Table 1-2.

[0080] b. Salt spray test: According to SH / T 0081-1991 "Salt spray test method for rust-proof grease", 45# steel is coated with rust-lubricating chain wax, and the test is carried out for 120 days. The test results are shown in Table 1-2;

[0081] (8) Extreme pressure test: According to GB / T 3142-2019 "Determination of load-bearing capacity of lubricants - Four-ball method", the test is carried out using a four-ball testing machine by changing the load size to detect the maximum no-seizure load P B and sintering load P D , P B Under this load, the ink on the friction surface can remain intact. If this load is exceeded, the oil film will break and the friction on the friction surface will increase sharply. B Indicates oil film strength, test results are shown in Table 1-2;

[0082] (9) Wear spot diameter: tested according to SH / T 0189-2017 “Determination of anti-wear properties of lubricating oils by four-ball method”, treated at 441N and 294N for 60 min respectively. The test results are shown in Table 1-2;

[0083] (10) High temperature coking performance: tested according to RH02ZB.0010-20044, the test results are shown in Table 1-2;

[0084] Table 1: Statistical table of performance test data of Examples 5-7

[0085]

[0086]

[0087] Table 2: Comparative Examples 4-7 Performance Test Data Statistics

[0088] Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 <![CDATA[Penetration at non - working condition / 10 -1 mm]]> 383 384 386 388 Dropping point / ℃ 252 264 258 278 <![CDATA[45 # Steel corrosion (100℃, 3h)]]> qualified qualified qualified qualified Adhesion / % 89 92 94 93 Water resistance (normal temperature) / % 9.4 6.1 7.1 5.2 Oxidation induction period / min 348 356 343 361 Wet heat test / d Not passed Not passed pass pass Salt spray test / d Not passed pass Not passed pass <![CDATA[The maximum non-seizure load P B / N]]> 588 643 634 678 <![CDATA[Sintering load P D / N]]> 4012 4450 4328 4613 Wear spot diameter D(441N) / mm 0.56 0.53 0.54 0.51 Wear spot diameter D(294N) / mm 0.49 0.42 0.44 0.40 Inclined plate coking / mg 5.5 4.4 4.9 2.6

[0089] As can be seen from Tables 1-2, the present application prepares Examples 5-7 by adding the prepared functional additives to the chain wax. The chain wax prepared in Examples 5-7 is tested according to SH / T 0331-1992 "Grease Corrosion Test Method", and the corrosion performance of the chain wax to steel passes the test, ensuring that the chain wax prepared in the present application has low corrosion to steel.

[0090] The chain wax prepared in Examples 5-7 of the present application is tested according to Appendix A of SH / T 0496 and has excellent adhesion properties. The chain wax attached to the surface of the chain will not be centrifugally thrown out during the high-speed operation of the motorcycle, effectively reducing the occurrence of rapid damage to the chain due to dry friction caused by the throwing out of grease during the operation of the chain.

[0091] The chain wax prepared in Examples 5-7 of the present application is tested according to SH / T 0109-1992 "Method for Determining the Water-Resistance Performance of Lubricating Greases" to ensure that the chain of the motorcycle is subjected to water and mud scouring during use and has excellent water-resistance performance.

[0092] The chain wax prepared in Examples 5-7 of the present application is tested according to SH / T 0193 "Determination of oxidation stability of lubricating oil (rotating oxygen bomb method)" to ensure that the chain wax is kept at a high temperature of 100-150°C for a long time and will not oxidize rapidly. The chain wax prepared in the present application has excellent antioxidant properties.

[0093] The chain wax prepared in Examples 5-7 of the present application was tested according to GB / T 2361-1992 "Wet Heat Test Method for Rust-Proof Greases". The functional additives prepared in the present application act synergistically with other components of the chain wax to give the chain wax good anti-rust properties such as resistance to salt spray and moisture and heat.

[0094] The chain wax prepared in Examples 5-7 of the present application was tested according to GB / T 3142-2019 "Determination of the load-bearing capacity of lubricants by four-ball method" and SH / T 0189-2017 "Determination of the anti-wear performance of lubricants by four-ball method", and the wear spot diameter was low and the maximum no-seizure load P was B And the sintering load P D High, it can be seen that the chain wax prepared in this application effectively improves the surface characteristics of the chain and reduces the surface roughness of the chain. The functional additive prepared in this application gives the chain wax a low friction coefficient and good anti-friction performance under a certain load, has automatic repair ability, and gives the material excellent wear resistance and friction reduction performance.

[0095] The chain wax prepared in Examples 5-7 of the present application is tested according to RH02ZB.0010-20044. The chain wax prepared in the present application is used under conditions of high temperature and full contact with air. The material has good resistance to high-temperature coking, which can effectively prevent the material from being blocked from moving between chain links due to coking, causing increased wear and affecting the smooth operation of the device.

[0096] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. A motorcycle anti-rust lubricating chain wax, characterized in that: The invention comprises the following raw materials in weight percentage: 67-93.5% base oil, 5.1-25.6% complex lithium soap thickener, 2.4-10.5% tackifier, 0.1-2% antioxidant, 0.5-5% extreme pressure anti-wear agent, 0.5-5% functional additive, 0.05-1% metal passivator, and the sum of the weight percentages of the raw materials is 100%; The preparation method of the functional additive comprises the following steps: S1: Add nano-silicon dioxide, aniline and hydrochloric acid solution into a reaction kettle, mix ammonium persulfate and distilled water evenly and add them into the reaction kettle, react at room temperature for 18-24 hours, filter, wash with acetone, and dry to obtain component 1; S2: Add component 1, thioglycolic acid and anhydrous ethanol into a reaction kettle, control the temperature to 50-60°C, keep warm for 1-3 hours under stirring conditions, filter, wash and dry to obtain a functional additive.

2. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The hydrochloric acid solution in S1 is a 0.5-1 mol / L hydrochloric acid aqueous solution; the addition ratio of nano-silicon dioxide, aniline, hydrochloric acid solution, ammonium persulfate, and distilled water is 10g: 1-2g: 500-1000mL: 3-6g: 100-200mL.

3. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The addition ratio of component 1, thioglycolic acid and anhydrous ethanol in S2 is 10g:0.5-1g:100-200mL.

4. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The base oil is any one of a polyether base oil and a paraffin base oil.

5. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The preparation method of the composite lithium soap thickener comprises the following steps: C1: Add lithium hydroxide powder and deionized water into a reaction kettle, control the temperature at 70-80°C, and stir until the lithium hydroxide powder is completely dissolved to obtain a lithium hydroxide solution; C2: Add 12-hydroxystearic acid and sebacic acid into the reaction kettle and disperse them evenly. Control the temperature at 95-105°C, add lithium hydroxide solution, and saponify for 1-3 hours under heat preservation conditions to obtain a composite lithium soap thickener.

6. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The tackifier is one of ethylene-propylene copolymer and polyisobutylene or a mixture of the two.

7. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The antioxidant is any one of an organic amine antioxidant or a phenolic antioxidant.

8. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The extreme pressure anti-wear agent is one or a mixture of two or more of phosphorus-containing compounds, sulfur-phosphorus compounds, and sulfur-phosphorus-nitrogen compounds.

9. The motorcycle anti-rust lubricating chain wax according to claim 1, characterized in that: The metal passivator is one or a combination of two or more of benzotriazole, benzotriazole derivatives, thiadiazole derivatives, and benzyl nickel phosphate.

10. A method for preparing a motorcycle anti-rust lubricating chain wax according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: adding base oil, composite lithium soap thickener and tackifier into a reaction kettle according to the raw material ratio, controlling the temperature at 95-105°C, keeping the temperature under stirring for 0.5-1h, controlling the temperature at 115-125°C, and vacuuming and dehydrating; then adding antioxidant, extreme pressure anti-wear agent, functional additive and metal passivator in sequence, stirring and mixing for 0.5-1.5h, naturally cooling, grinding and dispersing, and obtaining anti-rust lubricating chain wax.

Citation Information

Patent Citations

  • High-speed chain lubricating grease and preparation method thereof

    CN102965178A

  • Anticorrosive coating with polyaniline covering gas-phase nano-silica and preparation method thereof

    CN103205150A

  • Poly-o-aminobenzenethiol nanometer metal composite particle and preparation method

    CN104209536A

  • Preparation method and application of polyaniline-nano gold composite material

    CN105482450A

  • Composite shell material microcapsule with double anti-corrosion function and preparation method thereof

    CN109627826A